Study on mechanical characteristics of lumbar spine for snatch action in weight lifting based on finite element method - Bao, C.; Meng, Q. (International Journal of Sports Science and Engineering, 2010)
Objective: To establish the three-dimensional finite element model (FEM) of lumbar motion segment (L1-L2), to investigate mechanical characteristics of lumbar spinal motion segment for application of clinical diagnosis and therapy in weightlifters snatch. Methods: The three-dimensional FEM of lumbar spinal motion segment (L1-L2) with material properties and geometrical behaves was established, the biomechanical characteristics of lumbar spine was analyzed based on the finite element method at neutral position in snatch. Results: The three-dimensional FEM of lumbar spine (L1-L2) was directly established by Dicom data, the biomechanical characteristics of lumbar spine was studied at neutral position in snatch. Conclusion: the advantages of the method in the paper: fast speed of modeling, high precision of model; the FEM simulated the structure and materials properties of lumbar spine with geometrical, materials and nonlinear contact properties. In the standing position in snatch, stress acted on vertebral body was distributed on facet joints and pedicle of vertebral arch, stress concentration on inervertebral disc was found on middle-posterior location of annulus fibrosus, displacement centered mainly around posterior exterior location of intervertebral disc; at the moment, if the weight of barbell is too heavy and the lumbar muscle lacks of strength, it can cause lumbar joint instability and induce intervetebral disc excessive extrusion. The forward excessive shear stress on isthmus from the effects of gravity can cause isthmus injury. The three-dimensional finite element model of lumbar spine L1-L2 can be applied as a good tool in many fields in vertebral column biomechanics.